PENERAPAN MODEL PEMBELAJARAN INQUIRY TRAINING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS (KPS) IPA FISIKA SISWA KELAS VII SMP - Palma Juanta; Marlince NK Nababan; Apriani Sijabat; Yohandri Yohandri; Festiyed Festiyed (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The purpose of this study was to determine Science Process Skills (KPS) by applying the learning model to class VII materials on Temperature and Heat at Dr. Private Middle School. Wahidin Sudirohusodo for the 2022/2023 Academic Year conducted this research against the background of the low Science Process Skills (KPS) in Science for the last five years to 2021/2022, so that student learning outcomes were unsatisfactory. This was because students considered Science to be a difficult subject, especially Science Physics because it is necessary to use learning methods and models that can improve students' science process skills. This study used the classroom action research (PTK) method whose model was developed by Kemmis and McTaggart. Data collection techniques in this study used pretest and posttest test instruments with a population of 210 students spread across 7 parallel classes and one class was taken with 30 students as a sample. Data analysis using descriptive analysis was carried out by interactive analysis. The use of the inquiry training learning model has a good influence on improving science process skills. The research was conducted in pre-cycle and two cycles. In the pre-cycle with the pretest with a completeness score of only 16.67%, in the first cycle the completeness was 76.67%. Then the learning improvement was carried out again in cycle II, with inquiry training, completeness 83.33% So there was an increase in students' Science Process Skills.